Ruthenium–Ruthenium‐Bonded [Biscorrolato‐ruthenium(III)]n (n=0, +1, −1) Complexes: Model Compounds for the Photosynthetic Special Pair. Issue 10 (23rd January 2017) - Sinha, Woormileela; Sommer, Michael G.; Hettmanczyk, Lara; Patra, Bratati; Filippou, Vasileios; Sarkar, Biprajit; Kar, Sanjib
Abstract: We present herein the synthesis of three new bis(corrolato‐ruthenium(III)) complexes containing unsupported Ru–Ru bonds and their characterization in different redox states. The 1 H NMR spectra of the bis(corrolato‐ruthenium(III)) complexes displayed "normal" chemical shifts and the compounds proved to be EPR‐silent. Crystallographic characterization of the dimers indicated Ru–Ru distances of 2.175 Å, consistent with a triple bond between the two ruthenium centers. All of the synthesized complexes undergo two successive reversible oxidations and a single reversible reduction. A combination of UV/Vis/NIR/EPR spectroelectrochemical studies and DFT calculations established the redox state distributions in these ruthenium–ruthenium‐bonded dimers. Whereas reduction of the dimers is metal‐based and leads to metal‐metal‐bonded mixed‐valent Ru II –Ru III species, one‐electron oxidation largely retains the Ru III –Ru III situation with the generation of metal‐bound corrolato radicals. The present study thus concerns the first UV/Vis/NIR/EPR spectroelectrochemical characterization and DFT calculations of ruthenium–ruthenium‐bonded rotationally ordered corrole dimers. The mean plane separation between the two corrole units in these dimers is around 3.543 Å, which is in close agreement to that in the "special pair" in chlorophyll. Oxidation of these ruthenium–ruthenium‐bonded dimers gives rise to two new electronic absorption bands in the NIR region (similar to those of the special pair), which have apparently not been mentioned/observed in earlier reports on ruthenium–ruthenium‐bonded corrole dimers. These bands mainly originate from inter‐corrole transitions. Abstract : Mimicking the special pair : A series of ruthenium–ruthenium‐bonded dimeric corrole complexes has been prepared (see figure). Upon one‐electron‐oxidation of these complexes, the Ru III –Ru III situation is largely retained, and metal‐bound corrolato radicals are generated. Two NIR bands at 1064 nm (LMCT‐type) and 2315 nm (ILCT‐type) are seen for a representative oxidized complex, which closely resemble those originating from the radical cations of the photosynthetic "special pair".